Diálogos intergeracionais na formação inicial de monodocentes: o que dizem os estudantes? (Revista Lusófona de Educação, 2026)
In this article, we analyze the contributions of intergenerational dialogues (ID) to the development of teacher professionalism in the initial training of single-subject teachers. A case study is presented of two experiences developed at the start of the Bachelor's Degree in Basic Education (LEB): 1) in the first-year classes where students listened to professional stories in the first person from early childhood educators and primary school teachers (1st CEB); 2) in the FYT-ID Fifty Years of Teaching Project, where second-year students interviewed early childhood educators or primary school teachers (1st CEB). The analysis of the narratives of twelve students (six from each context), supported by Evans' (2014) dimensions of professionalism and emerging themes, allowed us to understand the meanings attributed to the dialogues and interactions with committed early childhood educators and primary school teachers. The narratives highlight the strong formative experience of the IDs and address the various components of professionalism, although there is greater prominence in the attitudinal component, followed by the behavioral and, finally, the intellectual. The appreciation of teachers as role models, perceptions of current challenges in the profession, and relationships between students' own biographies and professional projects also emerged. The study points to the need to include intergenerational dialogues early in initial training in the form of professional narratives capable of engaging students in the emotional, affective, and social dimensions of the profession for the intellectual or behavioral components of the profession but also for the attitudinal component that incorporates emotional, affective, and social dimensions of the profession, allowing for a more humanized training.Keywords: Intergenerational dialogues; Initial teacher education; Narrative research; Teacher professionalism.